2007
DOI: 10.1177/0091270006293755
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antidiabetic Drugs: Bioavailability Assessment of Fixed‐Dose Combination Tablets of Pioglitazone and Metformin. Effect of Body Weight, Gender, and Race on Systemic Exposures of Each Drug

Abstract: Bioavailability of pioglitazone and metformin, in 2 dose strengths, given either as a fixed-dose combination tablet or as coadministration of commercial tablets (coad), was studied in young healthy subjects in 2 separate studies. In study I (n = 63), single oral doses of 15-mg pioglitazone/500-mg metformin fixed-dose combination tablets or equivalent doses of commercial tablets were administered, in a fasting state, in an open-label, randomized, crossover study with a 7-day washout period between treatments. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
3
17
0
1
Order By: Relevance
“…7) Although the findings in our study differ from what is reported in prescribing information, they are consistent with a report by Karim and colleagues, which showed no effect of sex or body weight on the pharmacokinetics of pioglitazone after oral administration in healthy volunteers. 20) These investigators also reported no differences in pioglitazone plasma exposure between Caucasians, Blacks, and hispanics. 20) Unfortunately, we could not assess the effects of race or ethnicity on pioglitazone disposition in the population given that all of the subjects were Caucasian.…”
Section: Discussionmentioning
confidence: 94%
“…7) Although the findings in our study differ from what is reported in prescribing information, they are consistent with a report by Karim and colleagues, which showed no effect of sex or body weight on the pharmacokinetics of pioglitazone after oral administration in healthy volunteers. 20) These investigators also reported no differences in pioglitazone plasma exposure between Caucasians, Blacks, and hispanics. 20) Unfortunately, we could not assess the effects of race or ethnicity on pioglitazone disposition in the population given that all of the subjects were Caucasian.…”
Section: Discussionmentioning
confidence: 94%
“…Using an intrasubject coefficient of variation of 22% for C max and 19% for AUC based on published data on pioglitazone (Karim et al, 2007), a sample size of 12 subjects was considered sufficient for point estimates of the geometric mean ratios (GMRs) of C max and AUC, with and without coadministration of abiraterone acetate, to fall within 85% and 117% and within 87% and 115% of their true values, respectively, with 90% confidence. A sample size of 16 subjects was planned, assuming a dropout rate of 25%.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In the clinical trial mentioned above, pioglitazone in combination with metformin was shown to have similar pharmacokinetic properties in healthy non-Hispanic white, African American, and Hispanic populations 28 . In a non-randomized study consisting of African Americans with IGT and T2DM, rosiglitazone increased post-glucose challenge hepatic insulin extraction, and glycemic control was improved, but not normalized 34 .…”
Section: Thiazolidinedionesmentioning
confidence: 99%
“…Antihyperglycemic therapy typically begins with metformin. The drug has been relatively well studied among racial and ethnic minorities, and clinical findings have demonstrated similar pharmacokinetic properties in healthy non-Hispanic white, African American, and Hispanic populations when metformin is given with pioglitazone 28 . Recent observational data for 19,672 patients suggest that African Americans may respond to metformin treatment better than non-Hispanic white Americans 29 .…”
Section: Biguanides: Metforminmentioning
confidence: 99%